2009
DOI: 10.1073/pnas.0811734106
|View full text |Cite
|
Sign up to set email alerts
|

Incremental steps toward incompatibility revealed by Arabidopsis epistatic interactions modulating salicylic acid pathway activation

Abstract: Plant growth is influenced by genetic factors and environmental cues. Genotype-by-environment interactions are governed by complex genetic epistatic networks that are subject to natural selection. Here we describe a novel epistatic interaction modulating growth in response to temperature common to 2 Arabidopsis recombinant inbred line (RIL) populations (Ler ؋ Kas-2 and Ler ؋ Kond). At 14°C, lines with specific allele combinations at interacting loci (incompatible interactions) have severe growth defects. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
220
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(226 citation statements)
references
References 38 publications
(49 reference statements)
6
220
0
Order By: Relevance
“…Genetic mapping of stunted growth and necrotic phenotypes for a small subset of these crosses using laboratory strains such as Col and Ler as one of the parents implicated epistasis between a few loci involved in pathogen defense (Bomblies et al, 2007;Alcázar et al, 2009). These stunted and necrotic phenotypes are likely to have negative effects on fitness, such as we observed here, but relative fitness (fruit and seed production) of the F 1 has not been quantified for most of the crosses reported in Bomblies et al (2007).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Genetic mapping of stunted growth and necrotic phenotypes for a small subset of these crosses using laboratory strains such as Col and Ler as one of the parents implicated epistasis between a few loci involved in pathogen defense (Bomblies et al, 2007;Alcázar et al, 2009). These stunted and necrotic phenotypes are likely to have negative effects on fitness, such as we observed here, but relative fitness (fruit and seed production) of the F 1 has not been quantified for most of the crosses reported in Bomblies et al (2007).…”
Section: Discussionmentioning
confidence: 51%
“…Subsequent quantitative trait loci (QTL) mapping using Col as one of the parental lines indicated that the genetic basis of necrosis was due to negative epistatic interactions involving 2-4 loci (Bomblies et al, 2007). Similar interactions, mapped to approximately the same regions, were found in a study of the genetic basis of necrosis in two different recombinant inbred line mapping populations with Ler as a parental line (Alcázar et al, 2009).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We fine-mapped HWC2 gene in rice, and narrowed down the area of interest to 19 kb, identifying five candidate genes, one of which encodes an NB-LRR protein (Kuboyama et al 2009). Alcázar et al (2009) fine mapped a causal gene of incompatibility or hybrid breakdown to a cluster of TIR-NB-LRR genes in Arabidopsis. Yamamoto et al (2010) reported that hbd3, a causal gene controlling hybrid breakdown in rice, is located on the cluster of NB-LRR genes.…”
Section: T14×(t65×ptb7)]mentioning
confidence: 99%
“…Similar to the F 1 cases, these plants were strongly resistant to pathogen attack, and this depended on the defence hormone salicylic acid (SA). Remarkably, one of the responsible genes appears to be a distinct allelic variant at the same TIR-NB-LRR cluster as DM2 (Alcázar et al 2009). Since there are over 100 NB-LRR loci in the A. thaliana genome, this might indicate that not all of these are equally likely to cause hybrid problems.…”
Section: Intraspecific Incompatibilitymentioning
confidence: 99%